Phytochemicals and antioxidants capacity from some food products in Egypt and Sudan - Gina Fahim Mikhail Abdelmalek; Amira Shawky Soliman; Shaker Shehata Rizk; Sohair Ahmed Ismail Arafa (Cairo : Gina Fahim Mikhail Abdelmalek, 2020)
Studies on some types of natural antioxidants as polyphenols, flavonoids, lycopene and carotenoids in some tomatoes and carrots products as slices and sheets through four months storage periods and juices mixture through three months storage periods. Also, sensorial evaluation study was investigated. - Tomatoes fruits (Marwa species) and yellow carrots roots (Shanta species) material and methods were described. - Moisture, nitrogen free extract, fiber, oil, protein and vitamin C were determined, in fresh tomatoes and carrots. Two tomatoes products were process.- Tomatoes slices. - Tomatoes sheets. Moisture, acidity, vitamin C, total flavonoids, carotenoids, lycopene contents studied during storage 4 months. Also, pectin methyl esterase, viscosity were determined whereas, sensorial evaluation was studied in all products (10- panelist). Vegetable juices produced in tomato and carrot juices for each juices, also mixture produced by different percentage. Total phenolic compounds, flavonoids and carotenoids were determined in all mixture during 3 months storage
Thesis (Ph.D.) - Cairo University - Faculty of African Postgraduate Studies - Department of Natural Resources
Issued also as CD
Keywords: Antioxidants capacity; Food products; Phytochemicals